PENGARUH PEMBERIAN INFORMASI TERHADAP PEMAHAMAN REMAJA TENTANG PENDIDIKAN SEKSUAL DI SMP N 17 BATAM TAHUN 2017 - Natalia, Sandra; Aryaneta, Yenni (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
It is often that youth people vulnerably get sexual abuse due to lack of information on self-protection guidelines against the sexual harassment. From several cases of the harassments experienced by the teenager, the ratio of the occurrence were high which was noted up to 50% numbers, such as 80% abuse by the dirty verbal talks, 66% by the gaze full of sexual desire, 52% through certain body part as the sexual symbols, and 56% in form of the sexual seduction. Meanwhile, the harassments with the direct physical contacts had reached the level of 20 % of the teen-age girls. Thus, in this study, the researchers intend to see the impacts of the sex education provision to the knowledge levels of students mainly in handling the sexual harassment. This study employed pretest-posttest one group design using purposive sampling to derive 100 respondents as the sample which conducted from February 2016 to July 2017. The result of the analysis reveals the average score on before sex education provision is 15.67 and after the education accomplished is 24.74. Further, the result of the T-test obtains p-value = 0.00 (p<0.05). This finding indicates a significance difference on the average score on before and after the sex education provision. Therefore, it can be concluded that providing sex education for the students helps a lot in increasing the understanding and knowledge levels of students about sex.Â